Efficacy and safety of postoperative adjuvant HAIC combining lenvatinib with or without PD-1 inhibitors in solitary large HCC: A multicenter retrospective study - Liang, Yuxin; Wang, Ming; Zhong, Deyuan; Yan, Hongtao; Su, Yuhao; Chen, Xing; Huang, Xiaolun; Leng, Zhengwei (Frontiers in Immunology, 2025)
PurposeTo evaluate the efficacy and safety of postoperative adjuvant hepatic arterial infusion chemotherapy (PA-HAIC) combined with lenvatinib and PD-1 inhibitors versus PA-HAIC with lenvatinib alone in patients with solitary large hepatocellular carcinoma (HCC, >5 cm).MethodsA total of 183 patients who underwent curative resection and subsequent PA-HAIC plus lenvatinib (HAIC-L, n = 108) or PA-HAIC combined with lenvatinib and PD-1 inhibitors (HAIC-L-P, n = 75) were enrolled from three centers between April 2021 and April 2023. Propensity score matching (PSM) was applied to balance baseline characteristics. Disease-free survival (DFS) and overall survival (OS) were analyzed using the Kaplan–Meier method and Cox proportional hazards models, while treatment-related adverse events (TRAEs) were compared between groups.ResultsThe HAIC-L-P group demonstrated significantly improved DFS compared to the HAIC-L group both before (HR: 0.570; P = 0.007) and after PSM (HR: 0.518; P = 0.018). In contrast, no statistically significant difference was observed in OS between the two groups. Multivariate analysis identified elevated AFP (≥400 ng/mL), microvascular invasion, and treatment strategy (HAIC-L vs. and HAIC-L-P) as independent predictors of DFS. Additionally, the overall safety profiles were comparable, with similar incidences of TRAEs and no significant increase in hepatic toxicity with PD-1 inhibitor addition.ConclusionPA-HAIC combined with lenvatinib and PD-1 inhibitors significantly enhances DFS in patients with solitary large HCC, offering a promising adjuvant approach with acceptable safety. Further prospective, biomarker-driven trials are warranted to validate these findings and optimize patient selection.